Functional Diversity of Nectary Structure and Nectar Composition in the Genus Fritillaria (Liliaceae) - Roguz, Katarzyna; Bajguz, Andrzej; Gołębiewska, Agnieszka; Chmur, Magdalena; Hill, Laurence; Kalinowski, Paweł; Schönenberger, Jürg; Stpiczyńska, Małgorzata; Zych, Marcin (Frontiers in Plant Science, 2018)
Fritillaria is a genus of 130 to140 species of bulbous plants, native to temperate regions of the Northern Hemisphere. Generally viewed as an insect pollinated genus with the exception of two North America species, F. gentneri and F. recurva, which are described as hummingbird-pollinated and the Asian species, F. imperialis, described as passerine-pollinated. These pollinating shifts are possibly the result of adaptive changes to the structure and morphology of the nectary, as well as a change in the nectar concentration and composition. A study was conducted in a target group of 56 Fritillaria species of the morphology of their nectaries and nectar composition to assess the significance of pollination mode as well as its predisposition for the evolution of bird pollination. All species studied had nectaries located at their tepal base and produced nectar but size, shape, colour and composition all varied. Most fritillaries had hexose-rich nectar, in easily accessible, unprotected nectaries. SEM analysis revealed that the surface of nectaries of most Fritillaria was flat and clearly distinct from that of surrounding tissues, which might be regarded as an adaptation for insect-pollination. Nectaries of and F. imperialis were considerably larger, have dilute nectar without sucrose, which was produced profusely, thereby fulfilling criteria characteristic for ornithophilous flowers. The copious nectar of presumed humming-bird pollinated species was rather balanced and of medium sugar concentration. Their large lanceolate nectaries contrasted sharply with the tessellated background of their tepals. These characters might indicate a mixed pollinated system that engages both birds and insects. Floral anatomy and microstructure and nectar composition for Fritillaria species in subgenera Korolkowia and Liliorhiza are studied for the first time.